2020
DOI: 10.1111/nuf.12497
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding bad connection: Orientation phone calls foster student‐faculty connection in an RN‐BSN program

Abstract: Background Studies show that the primary reasons registered nurses (RNs) withdraw from registered nurse to bachelor of science in nursing (RN‐BSN) programs are related to the challenge of sustaining work and family obligations while in school and having unclear expectations. It has been shown that nontraditional students facing these types of challenges benefit from programs that give strong sense of faculty connection and orient students to coursework by providing clear information. Purpose The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As relationships develop between students and faculty and a supportive environment evolves, students are more likely to reach their academic goals. 26 Identifying additional platforms and technology to enhance engagement between students and faculty allows for the development of the distance learning community. 27 Collaborative learning supports the academic socialization process and facilitates the sense of social presence in the classroom environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As relationships develop between students and faculty and a supportive environment evolves, students are more likely to reach their academic goals. 26 Identifying additional platforms and technology to enhance engagement between students and faculty allows for the development of the distance learning community. 27 Collaborative learning supports the academic socialization process and facilitates the sense of social presence in the classroom environment.…”
Section: Discussionmentioning
confidence: 99%
“…As we consider the focus of Tinto's9,14 work, Let's Check-In: Tips for Success provides us the opportunity to connect with the students through the building of relationships and establishing a social presence, often missing in the online environment. As relationships develop between students and faculty and a supportive environment evolves, students are more likely to reach their academic goals 26…”
Section: Discussionmentioning
confidence: 99%
“…1 In another study, researchers found when faculty phoned first-semester online postlicensure students after the in-person orientation, students reported feeling a sense of connectedness and being well-prepared for the program. 2 In a third study, a comprehensive orientation along with other retention strategies designed to improve the student persistence for associate degree nursing students was proven effective. 3 Prior to July 2017, prelicensure nursing students at a large university in southwestern United States received 2 full days of program orientation.…”
Section: Introductionmentioning
confidence: 98%
“…In one study, the use of in-person orientations for online postlicensure students improved retention rates and increased the students' confidence level in the online environment 1. In another study, researchers found when faculty phoned first-semester online postlicensure students after the in-person orientation, students reported feeling a sense of connectedness and being well-prepared for the program 2. In a third study, a comprehensive orientation along with other retention strategies designed to improve the student persistence for associate degree nursing students was proven effective 3…”
Section: Introductionmentioning
confidence: 99%